Question

( left(x y^{2}+xright) d x+left(y x^{2}+yright) d y=0 )
( x d xleft(y^{2}+1right)=-y d yleft(x^{2}+1right) )
( frac{x}{x^{2}+1} d x=frac{-y}{y^{2}+1} d y )
Integrating both sides
( int frac{x}{x^{2}+1} d x=-int frac{y^{2}}{y^{2}+1} d y )
( Rightarrow frac{log left|x^{2}+1right|}{2}=-frac{log left|y^{2}+1right|}{2}+C^{prime} )
( Rightarrow operatorname{cog}left|x^{2}+1right|+log left|y^{2}+1right|=c )

# Solve the following differential equations: 1. (xy2 + x)dx + (yx² + y)dy = 0.

Solution